(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Various writers in Nashik District are engaged in Book publication activity. No comprehensive list of such books is available. This creates problems in bibliographic control. The researcher intends to list the books published in 2005 to 2007 in Nashik District.The research paper will be defiantly helpful not only to the researchers but also students and Booksellers. This research will also be helpful in getting period-wise publication data of time. This research also helpful in getting tahasil-wise list of published Book.